Preparation method of self-supporting three-dimensional electrocatalyst with adjustable pore structure and ordered metal distribution

Through the preparation methods of self-support, adjustable channel structure, orderly metal distribution, and three-dimensional electrocatalyst, the problems of high cost, low efficiency and insufficient long-term stability of the existing electrolytic hydrolysis hydrogen catalyst are solved, and low cost and high efficiency are achieved , a catalyst with good long-term stability, suitable for hydrogen production by water electrolysis.

CN119465245AActive Publication Date: 2025-02-18CHINA UNIV OF PETROLEUM (BEIJING) +1

Patent Information

Application Number
CN202411491585.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-18
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Existing hydrogen production catalysts with water electrolysis method have problems such as high cost, low efficiency and insufficient long-term stability, especially the reserves of precious metal catalysts are limited and the price is high, the catalytic activity of non-metal-based catalysts is limited, and the transition metal-based catalyst support materials are supported. Difficult to regulate structure.

Method used

The preparation method of self-support, adjustable pore structure, orderly distribution of metals, and three-dimensional electrocatalysts is adopted. By adjusting raw material ratio, changing the direction of freezing, controlling the type of reaction monomer and calcining temperature, the precise regulation of pore size and pore structure is achieved to ensure the metal. Directional distribution of nanoparticles and optimization of the conductivity of the carrier.

Benefits of technology

It realizes a low-cost, high-efficiency, and good long-term stability of electrocatalysts, reduces the proportion of precious metals, increases the metal adsorption site and active center of the catalyst, is suitable for hydrogen production by water electrolysis, and has good expansion and environmental friendliness. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005100223240000011
    Figure HDA0005100223240000011
  • Figure HDA0005100223240000012
    Figure HDA0005100223240000012
  • Figure HDA0005100223240000021
    Figure HDA0005100223240000021
Patent Text Reader

Abstract

The invention discloses a preparation method of a self-supporting three-dimensional electrocatalyst with an adjustable pore structure and ordered metal distribution. The method is divided into the following two methods according to different adding steps of metal nanoparticles or metal precursors: the method I comprises the following steps: 1) preparing a porous organic polymer by adopting an ice template method; 2) dissolving a metal precursor in an ethanol solution at room temperature, mixing with the porous organic polymer carrier, and standing until ethanol is completely volatilized to obtain a porous organic polymer with orderly distributed metals; and 3) performing high-temperature carbonization on the porous organic polymer with orderly distributed metals to obtain the porous organic polymer. The method II comprises the following steps: a) preparing a porous organic polymer with orderly distributed metals by adopting an ice template method; and b) carrying out high-temperature carbonization on the porous organic polymer with orderly distributed metals. The application of the porous organic polymer material in the fields of catalysis, composite material modification, supercapacitors and the like in other fields can be expanded through copolymerization or addition of functional fillers (such as magnetic particles, conductive fillers and the like).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a method for preparing a three-dimensional electrocatalyst which is self-supporting, has an adjustable pore structure, and has orderly metal distribution. Background Art

[0002] With the development of society, traditional energy has brought serious environmental pollution problems while prospering the economy, hindering the sustainable development of human society. In order to solve these problems, the development of new energy is becoming a research hotspot. Hydrogen, as an ideal energy source, has the advantages of high calorific value and green and pollution-free combustion products, and has attracted widespread attention from all over the world. However, most of the hydrogen in China is still highly dependent on industrial devices of fossil raw materials, such as coal-to-hydrogen, natural gas-to-hydrogen, industrial by-product hydrogen, etc. Although these traditional industrial devices have simple hydrogen production processes, the hydrogen obtained is of low purity and produces a large amount of greenhouse gas CO2, which does not meet the requirements of green industrial development in today's society. Hydrogen production by water electrolysis (HER) does not rely on fossil fuels, and the only raw material used in large quantities is water; the device is simple, the system is mature, and it has industrial prospects; it can be used in conjunction with new energy sources such as photovoltaics and wind power, and can be used as a storage method for new energy electricity and an intermediate carrier for energy conversion, which is one of the important ways to clean energy conversion.

[0003] In the HER process, the development of electrocatalysts is the key. At present, HER catalysts are mainly divided into three categories: precious metal-based catalysts, transition metal-based catalysts and non-metal-based catalysts. Among them, precious metal catalysts have obvious excellent performance in HER catalysis, but due to the limited reserves of precious metals and high prices, the cost of industrial application is relatively high. In order to reduce the cost of use, there are a lot of studies on the use of non-metal-based or transition metal-based catalysts for replacement. Non-metallic catalysts are mainly carbon materials, which have the advantages of excellent conductivity, strong acid and alkali corrosion resistance, and adjustable structure. However, the intrinsic activity of carbon materials in catalyzing the electrolysis of water for hydrogen evolution cannot meet the needs of industrial applications. Generally, the catalytic activity of carbon materials is improved to a certain extent by methods such as non-metallic doping such as B, N, P and S or manufacturing defects, but the performance improvement is still very limited. Transition metal-based catalysts generally use metals or metal alloys such as Fe, Co, Ni, Mn, Mo as the active center of the catalyst, and are loaded on carriers such as nickel foam, porous carbon materials, and layered double hydroxides (LDH). This type of catalyst has the advantages of simple preparation method, low cost, and adjustable structure and composition, but it is very difficult to control the structure, pores and surface properties of the carrier material, resulting in weak interaction between the metal active center and the carrier, and the long-term stability of the catalyst needs to be further improved. Therefore, the development of a low-cost, high-efficiency, and long-term stable electrocatalyst is imminent. Summary of the invention

[0004] In view of the defects of the prior art, the present invention provides a method for preparing a self-supporting, pore structure-adjustable, metal-ordered distributed, three-dimensional electrocatalyst. This method can achieve precise control of pore size and pore structure by adjusting the raw material ratio and changing the freezing direction to meet different application requirements; by changing the type of reaction monomer, the internal and external surface properties are regulated to achieve directional, orderly, and uniform distribution of metal nanoparticles on its surface or inside; by changing the calcination temperature of the carrier, the conductivity, number and type of defects, and mechanical strength of the finally prepared three-dimensional, self-supporting, porous carbon carrier are regulated. This method has good scalability and is easy to dope with different metals and metal combinations. By doping with non-precious metals, the proportion of precious metals can be reduced, thereby reducing the cost of the catalyst, and on the other hand, the metal adsorption sites and active centers of the catalyst can be increased.

[0005] The method for preparing the self-supporting, tunable pore structure, orderly metal distribution, and three-dimensional electrocatalyst provided by the present invention is divided into the following two methods according to the different steps of adding metal nanoparticles or metal precursors.

[0006] Method 1:

[0007] 1) Porous organic polymers were prepared by ice template method;

[0008] 2) dissolving the metal precursor in an ethanol solution at room temperature, and mixing it with the porous organic polymer carrier obtained in step 1), stirring for 22 to 26 hours, and standing until the ethanol is completely volatilized to obtain a porous organic polymer with orderly metal distribution;

[0009] 3) Carbonizing the porous organic polymer with orderly metal distribution obtained in step 2) at high temperature to obtain the self-supporting, three-dimensional electrocatalyst with adjustable pore structure and orderly metal distribution.

[0010] In step 1) of the method one, the method for preparing the porous organic polymer specifically includes the following steps: preparing a polymer precursor emulsion, wherein the emulsion includes a reaction monomer, a redox initiator, a cross-linking agent, and a reactive emulsifier; subjecting the polymer precursor emulsion to low-temperature freezing molding; after molding, subjecting the frozen sample to low-temperature polymerization, and after the polymerization is completed, freeze-drying the frozen sample to remove the ice template to obtain a porous organic polymer.

[0011] Further, the reactive monomer may be selected from at least one of the following: methyl methacrylate (MMA), acrylonitrile (AN), methacrylamide (MAM), and butyl acrylate (BA); according to an embodiment of the present invention, the reactive monomer may be selected from: methyl methacrylate (MMA) and acrylonitrile (AN);

[0012] Furthermore, the redox initiator includes benzoyl peroxide (BPO) and N,N-dimethylaniline (DMA).

[0013] Further, the cross-linking agent may be selected from ethylene glycol dimethacrylate (EGDMA).

[0014] Furthermore, the reactive emulsifier may be selected from ADEKAREASOAP series, ER-10.

[0015] Furthermore, the low-temperature freezing molding can be performed by cooling the product to a desired shape using liquid nitrogen.

[0016] Furthermore, the reaction conditions of the low temperature polymerization are: low temperature polymerization at -15°C to -30°C for at least 12 hours. Under the low temperature polymerization conditions, the monomer droplets are completely coalesced and frozen polymerized.

[0017] According to one embodiment of the present invention, the method for preparing the porous organic polymer is as follows: 0.075g BPO (benzoyl peroxide, the amount corresponding to the total volume of the emulsion is 10mL) and 5% v / v (percentage of the total volume of the emulsion) EGDMA (ethylene glycol dimethacrylate) are mixed with 15% v / v (percentage of the total volume of the emulsion) of monomer (MMA:AN=1:1, v / v; MMA: methyl methacrylate, AN: acrylonitrile) to form a monomer phase (20% v / v of the total volume of the emulsion); ER-10 emulsifier and water are configured to form a 5% v / v (percentage of the volume of the aqueous phase) ER-10 solution as the aqueous phase. The monomer phase and the aqueous phase are mixed in a volume ratio of 2:8 to form a precursor emulsion, and ultrasonicated for 5 minutes (make sure the emulsion is cooled to below 4°C before use). After ultrasound, add 5% v / v (percentage of the total volume of the emulsion) of DMA (N,N-dimethylaniline) to the emulsion, stir vigorously for 1 minute, and immediately pour it into the mold and cool it with liquid nitrogen until it is formed. After forming, place the frozen sample in a -15°C environment for low-temperature polymerization for at least 12 hours. After the polymerization is completed, freeze-dry the frozen sample to remove the ice template to obtain a porous organic polymer.

[0018] In step 2) of the method 1, as the ethanol evaporates, the metal sol gradually concentrates, and finally forms a gel of metal particles or metal oxide particles that are deposited on the surface of the carrier. The size and distribution of the metal particles or metal oxide particles are controlled by controlling the ethanol volatilization rate and the stirring rate during the reaction, thereby achieving control of the loaded metal.

[0019] Furthermore, in the step 2), the volume fraction of ethanol in the ethanol solution is 90-99.9%.

[0020] Furthermore, in step 2), the concentration of the metal precursor in the ethanol solution is 8 mg / L-50 mg / L

[0021] In step 3) of method one, the high-temperature carbonization condition may be heating at a heating rate of 2-5°C / min under a nitrogen atmosphere, heating to 700-800°C and keeping warm for 2 hours. The organic ligands in the polymer material are pyrolyzed at high temperature to form a carbonaceous pore structure. These pore structures can provide good proton and electron transport channels, which are conducive to the catalytic reaction. At the same time, at high temperatures, metal ions will be reduced to metal nanoparticles. These metal nanoparticles have good dispersibility in the carbonaceous pore structure, and can participate in the catalytic reaction as catalyst active centers, and the final material is obtained after carbonization. Controlling the calcination temperature can regulate the electrical conductivity and mechanical strength of the material.

[0022] Method 2:

[0023] a) preparing a porous organic polymer with orderly metal distribution by ice template method;

[0024] b) carbonizing the porous organic polymer with orderly metal distribution obtained in step a) at high temperature to obtain the self-supporting, pore structure-adjustable, metal-ordered distributed, three-dimensional electrocatalyst.

[0025] The method a) directly adds metal nanoparticles or metal precursors during the preparation of the emulsion, mixes them with the emulsion and then freezes them at low temperatures, and controls the amount and type of the added metal nanoparticles or metal precursors to achieve uniform distribution of different metals on the carrier.

[0026] In step a) of the second method, the method for preparing a porous organic polymer with orderly metal distribution specifically includes the following steps: preparing a polymer precursor emulsion, wherein the emulsion includes a reaction monomer, a redox initiator, a cross-linking agent, a reactive emulsifier, metal nanoparticles or a metal precursor; subjecting the polymer precursor emulsion to low-temperature freezing molding; after molding, subjecting the frozen sample to low-temperature polymerization, and after the polymerization is completed, freeze-drying the frozen sample to remove the ice template to obtain a porous organic polymer with orderly metal distribution.

[0027] Further, the reactive monomer may be selected from at least one of the following: methyl methacrylate (MMA), acrylonitrile (AN), methacrylamide (MAM), and butyl acrylate (BA); according to an embodiment of the present invention, the reactive monomer may be selected from: methyl methacrylate (MMA) and acrylonitrile (AN);

[0028] Furthermore, the redox initiator includes benzoyl peroxide (BPO) and N,N-dimethylaniline (DMA).

[0029] Further, the cross-linking agent may be selected from ethylene glycol dimethacrylate (EGDMA).

[0030] Furthermore, the reactive emulsifier may be selected from ADEKAREASOAP series, ER-10.

[0031] Furthermore, the metal nanoparticles or metal precursors are selected from at least one of the following: nickel chloride, cobalt chloride, gallium chloride, rubidium chloride, and ruthenium trichloride. The concentration of the metal nanoparticles or metal precursors in the ethanol solution is 8 mg / L-50 mg / L.

[0032] Furthermore, the low-temperature freezing molding can be performed by cooling the product to a desired shape using liquid nitrogen.

[0033] Furthermore, the reaction conditions of the low temperature polymerization are: low temperature polymerization at -15°C to -30°C for at least 12 hours. Under the low temperature polymerization conditions, the monomer droplets are completely coalesced and frozen polymerized.

[0034] According to one embodiment of the present invention, a specific method for preparing a porous organic polymer with orderly metal distribution is as follows:

[0035] 0.075g BPO (benzoyl peroxide, the amount corresponding to the total volume of the emulsion is 10mL) and 5% v / v (percentage of the total volume of the emulsion) EGDMA (ethylene glycol dimethacrylate) are mixed with 15% v / v (percentage of the total volume of the emulsion) of monomer (MMA:AN=1:1, v / v; MMA: methyl methacrylate, AN: acrylonitrile) to form a monomer phase (20% v / v of the total volume of the emulsion); ER-10 emulsifier and water are configured to form a 5% v / v (percentage of the volume of the aqueous phase) ER-10 solution as the aqueous phase. The monomer phase and the aqueous phase are mixed in a volume ratio of 2:8 to form a precursor emulsion, and ultrasonicated for 5 minutes (make sure the emulsion is cooled to below 4°C before use). After ultrasound, add 5% v / v (percentage of the total volume of the emulsion) of DMA (N,N-dimethylaniline) and 10% v / v (percentage of the total volume of the emulsion) of 8mg / L to 50mg / L metal precursor ethanol solution to the emulsion, stir vigorously for 1 minute, pour into the mold immediately, and use liquid nitrogen to cool to shape. After molding, place the frozen sample in a -15°C environment for low-temperature polymerization for at least 12 hours. After the polymerization is completed, freeze-dry the frozen sample to remove the ice template to obtain a porous organic polymer with orderly metal distribution.

[0036] In step b) of the second method, the high-temperature carbonization condition may be heating at a heating rate of 2-5°C / min under a nitrogen atmosphere, heating to 700-800°C and keeping warm for 2 hours. The organic ligands in the polymer material are pyrolyzed at high temperatures to form a carbonaceous pore structure. These pore structures can provide good proton and electron transport channels, which are conducive to the catalytic reaction. At the same time, at high temperatures, metal ions will be reduced to metal nanoparticles. These metal nanoparticles have good dispersibility in the carbonaceous pore structure, and can participate in the catalytic reaction as catalyst active centers, and the final material is obtained after carbonization. Controlling the calcination temperature can regulate the electrical conductivity and mechanical strength of the material.

[0037] The self-supporting, three-dimensional electrocatalytic hydrogen production catalyst with adjustable pore structure and orderly metal distribution prepared by the above method also falls within the protection scope of the present invention.

[0038] The present invention also provides the application of the above-mentioned self-supporting, three-dimensional electrocatalyst with adjustable pore structure and orderly metal distribution.

[0039] The application is the application of self-supporting, adjustable pore structure, orderly metal distribution, and three-dimensional electrocatalyst in hydrogen production by water electrolysis.

[0040] The invention also provides a method for producing hydrogen by electrolyzing water.

[0041] The present invention provides a method for producing hydrogen by electrolyzing water, which adopts the self-supporting, pore structure-adjustable, metal-ordered distributed, three-dimensional electrocatalyst prepared by the present invention as an electrocatalyst.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] 1. When preparing porous materials, this method can control the direction and morphology of ice crystal growth, optimize the concentration, ratio and freezing process of initiators, cross-linking agents and emulsifiers, and achieve precise control of pore size and pore structure, which is convenient for the contact between materials and reactive active centers and mass transfer during the catalytic process.

[0044] 2. By changing the type of reactive monomers, the internal and external surface properties can be regulated to achieve directional, orderly and uniform distribution of metal nanoparticles on its surface or inside; by changing the calcination temperature of the carrier, the conductivity, number and type of defects, and mechanical strength of the final prepared three-dimensional, self-supporting, porous carbon carrier can be regulated.

[0045] 3. This method has good scalability and is easy to dope with different metals and metal combinations, making it easy to prepare bimetallic or even multimetallic ordered three-dimensional materials. By doping with non-precious metals, the proportion of precious metals can be reduced, thereby reducing the cost of the catalyst. In addition, by regulating the type of metal nanoparticles and the bonding force between them and the carrier, the metal adsorption sites and active centers of the catalyst can be improved, ultimately achieving the development of low-cost, high-efficiency, and long-term stable catalysts.

[0046] 4. This method uses ice as a template, which reduces the generation of chemical waste such as organic solvents and is more environmentally friendly.

[0047] 5. Porous organic polymer materials can be expanded to other fields such as catalysis, composite material modification, supercapacitors, etc. through copolymerization or adding functional fillers (such as magnetic particles, conductive fillers, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The principle of low-temperature emulsion polymerization: a) the reaction principle of the reaction monomer and emulsifier; b) the initiation process of the redox initiation system. The oxidized BPO and DMA react first, and the product of this reaction is unstable and easily generates free radicals at low temperatures, which initiates the polymerization process.

[0049] Figure 2 ab) controlled freezing of monomer / water emulsion: ice crystals continue to grow and monomer droplets are discharged; cd) placing the sample below -15°C for coalescence and low-temperature polymerization, c) coalescence, d) low-temperature polymerization; e) freeze drying to obtain a precursor; f) carbonization of the material.

[0050] Figure 3 Schematic diagram of the HER catalyst synthesis process (Method 1).

[0051] Figure 4 These are scanning electron microscope images of the cross sections of the porous polymer precursor materials prepared by method one (left side) and method two (right side) in the examples.

[0052] Figure 5 This is the EDS graph of C, N, O, and Ru of the catalyst obtained after carbonization by method 1 in Example.

[0053] Figure 6 This is the EDS graph of C, N, O, and Ru of the catalyst obtained after carbonization according to the method in the example.

[0054] Figure 7 HER catalytic activity of Ru / NC, Ru / C, Ru / XC72C, Pt / C, and NC (a) Linear voltammetric scan curve LSV; (b) Tafel curve and Tafel slope; (c) Enquist impedance diagram; (d) Active area comparison diagram.

[0055] Figure 8 The 1500 min stability test result of the HER catalyst (Ru / NC) prepared by method 2 in Example 1. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0057] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0058] Example

[0059] 1. Synthesis of HER catalyst (Method 1)

[0060] 1) 0.075g BPO (benzoyl peroxide, the amount corresponding to the total volume of the emulsion is 10mL) and 5% v / v (the percentage of the total volume of the emulsion) EGDMA (ethylene glycol dimethacrylate) are mixed with 15% v / v (the percentage of the total volume of the emulsion) of monomer (MMA:AN=1:1, v / v; MMA: methyl methacrylate, AN: acrylonitrile) to form a monomer phase (the total volume percentage of the emulsion is 20% v / v); ER-10 emulsifier and water are configured to form a 5% v / v (the volume percentage of the aqueous phase) ER-10 solution as the aqueous phase. The monomer phase and the aqueous phase are mixed in a volume ratio of 2:8 to form a precursor emulsion (10mL), and ultrasonicated for 5 minutes (make sure the emulsion is cooled to below 4°C before use). After ultrasonication, 5% v / v (the percentage of the total volume of the emulsion) of DMA (N,N-dimethylaniline) is added to the emulsion, stirred vigorously for 1 minute, and then immediately poured into a mold and cooled with liquid nitrogen to form a shape. After forming, the frozen sample was placed in a -15°C environment for low-temperature polymerization for at least 12 hours. After the polymerization was completed, the frozen sample was freeze-dried to remove the ice template to obtain a porous organic polymer.

[0061] 2) 1.0g of porous organic polymer precursor was immersed in an ethanol solution (the concentration of ruthenium chloride was 8.8mg / L, 26.4mg / L, 44mg / L) dissolved with different amounts of ruthenium trichloride (2.2mg, 6.6mg, 11mg), stirred for 24h, and then allowed to stand until the ethanol was completely volatilized to obtain a porous organic polymer with orderly metal distribution. Finally, the obtained polymer was placed in a tubular furnace, kept at 750℃ for 2h under a nitrogen atmosphere, and heated at a heating rate of 5℃ / min to obtain the final HER catalyst.

[0062] 2. Synthesis of HER catalyst (Method 2)

[0063] In the process of preparing the emulsion in the above method 1, metal nanoparticles or metal precursors are directly added, mixed evenly with the emulsion and then cryogenically frozen, and the uniform distribution of different metals on the carrier is achieved by controlling the amount and type of the added metal nanoparticles or metal precursors.

[0064] The specific method is as follows:

[0065] a) 0.075g BPO (benzoyl peroxide, the amount corresponding to the total volume of the emulsion is 10mL) and 5% v / v (percentage of the total volume of the emulsion) EGDMA (ethylene glycol dimethacrylate) are mixed with 15% v / v (percentage of the total volume of the emulsion) of monomer (MMA:AN=1:1, v / v; MMA: methyl methacrylate, AN: acrylonitrile) to form a monomer phase (20% v / v of the total volume of the emulsion); ER-10 emulsifier and water are configured to form a 5% v / v (percentage of the volume of the aqueous phase) ER-10 solution as the aqueous phase. The monomer phase and the aqueous phase are mixed in a volume ratio of 2:8 to form a precursor emulsion (10mL), and ultrasonicated for 5 minutes (make sure the emulsion is cooled to below 4°C before use). After ultrasound, add 5% v / v (percentage of the total volume of the emulsion) of DMA (N,N-dimethylaniline) and 10% v / v (percentage of the total volume of the emulsion) of metal precursor ethanol solution (concentrations are 8.8 mg / L, 26.4 mg / L, and 44 mg / L, respectively) to the emulsion, stir vigorously for 1 minute, and immediately pour into the mold and cool with liquid nitrogen until it is formed. After forming, place the frozen sample in a -15°C environment for low-temperature polymerization for at least 12 hours. After the polymerization is completed, freeze-dry the frozen sample to remove the ice template to obtain a porous organic polymer with orderly metal distribution.

[0066] b) placing the porous organic polymer with orderly metal distribution obtained in step a) in a tubular furnace, keeping the temperature at 750° C. for 2 h under a nitrogen atmosphere, and heating at a heating rate of 5° C. / min to obtain a final HER catalyst.

[0067] In the above preparation process, the size of the pores is controlled by adjusting the freezing temperature, using a copper plate as the freezing surface and liquid nitrogen as the cooling source. The vertical morphology of the porous polymer precursor is as follows: Figure 4 As shown. Figure 4 It can be seen that the organic polymer material prepared by the ice template forms longitudinal channels after the ice crystals are extracted, thereby preparing the desired porous organic polymer material.

[0068] By adjusting the emulsifier (ER-10) content to 0.1% v / v, 1% v / v, 5% v / v and 10% v / v (all represent the percentage of the volume of the aqueous phase), different sizes of emulsion droplets were formed, which affected the strength of the polymer precursor. When a small amount of emulsifier (0.1% v / v) was used, the emulsion droplets were larger, and during the ice growth process, the large droplets were difficult to discharge and aggregate, resulting in poor pore wall strength. Increasing the ER-10 concentration to 1% v / v formed a better emulsion, and these medium-sized droplets were effectively assembled into pore walls, but the residual ice particles sandwiched in the monomer droplets caused defects in the pore walls. When the ER-10 concentration was increased to 5% v / v, the emulsion droplets became smaller and the droplets were densely stacked, avoiding defects in the final pore wall and having the best compressive strength. At higher ER-10 concentrations (10% v / v), the self-polymerization of ER-10 led to weak areas in the pore wall and a reduction in compressive strength. Therefore, the ER-10 content was selected to be 5% v / v.

[0069] When selecting the reaction monomer, when the reaction monomer is only methyl methacrylate (MMA), there are fewer active sites. In order to achieve better hydrogen evolution performance, acrylonitrile (AN) is introduced to increase the active sites and make the distribution of metal nanoparticles more uniform.

[0070] At the same time, by changing the different calcination temperatures of the precursor, calcination was carried out at 700°C, 750°C, and 800°C. The precursor material calcined at 750°C has better conductivity, fewer defects, and the highest mechanical strength.

[0071] from Figure 5 As can be seen from the EDS-mapping diagram of Ru / NC prepared by method 1, the main body of the catalyst is mainly composed of C, in which the N element is evenly distributed on the carbon skeleton, indicating the successful doping of heteroatom nitrogen. In addition, there is a small amount of oxygen on the carbon carrier, which is due to the residual oxygen caused by the insufficient calcination temperature of the catalyst. In addition, the uniform distribution of Ru elements on the surface of the carbon carrier proves the successful loading of Ru nanoparticles.

[0072] from Figure 6As can be seen in the EDS-mapping diagram of Ru / NC prepared by method 2, the catalyst is similar to Ru / NC prepared by method 1. The main body is mainly composed of C and O, and the N element is evenly distributed on the carbon skeleton, indicating the successful doping of heteroatom nitrogen. The Ru element is also evenly distributed on the surface of the carbon support, proving the successful loading of Ru nanoparticles.

[0073] 3. Performance of HER catalyst for electrocatalytic hydrogen production

[0074] First, the electrochemical activity tests were carried out on Ru / NC (the catalyst obtained by impregnating 11 mg of ruthenium trichloride and doping with nitrogen in Example 1 and calcining at 750°C), Ru / C, Ru / XC72C (XC72C is commercial carbon black, Vulcan XC 72), Pt / C (commercial platinum carbon, Aladdin Reagent Co., Ltd.), and NC.

[0075] The preparation method of the above Ru / C is basically the same as that of Ru / NC, except that acrylonitrile (AN) is replaced by an equal amount of methyl methacrylate (MMA).

[0076] The above-mentioned Ru / XC72C uses XC72C as commercial carbon black to replace the porous organic polymer precursor in step 2) of the above-mentioned method 1, and the rest of the preparation method is the same as step 2) of method 1.

[0077] The above NC is a porous carbon material doped with nitrogen but not loaded with metal, that is, a porous organic polymer prepared in step 1) of the above method.

[0078] like Figure 7 As shown in (a), it is found that the NC sample shows almost no HER activity during the hydrogen evolution process. When the overpotential exceeds 500 mV, the current density still cannot reach 10 mA / cm 2 This further demonstrates that metal Ru is the active site of the catalyst. Ru / C catalyst has a high specific surface area and porous structure, which can show good electrochemical catalytic activity at low current density (10mA / cm 2 ) conditions, it exhibited a hydrogen evolution activity of 40.2 mV. Ru / NC catalyst, at 10 mA / cm 2 and 50mA / cm 2 The HER performances of Ru / C catalysts were 29.2mV and 109.2mV (the lower the overpotential, the better), respectively. 10 and η 50 The η of Ru / NC and Ru / N-XC72C increased by 11mV and 33mV respectively. Different carbon carriers also have a significant effect on the HER performance. By comparing Ru / NC and Ru / N-XC72C, it can be found that the η of Ru / N-XC72C 10 , η 50The catalytic performance is much lower than that of Ru / NC catalyst, which proves the advantages of the prepared porous material. Its high specific surface area and rich micropore and mesoporous structure provide a large amount of metal active site loading space and excellent mass transfer performance for the catalyst.

[0079] Finally, the HER performance of Ru / NC and commercial Pt / C catalysts was compared. 2 At a current density of , the commercial Pt / C catalyst exhibited an overpotential of 52.2 mV, which is much higher than that of the Ru / NC catalyst. In addition, the Ru / NC catalyst has a lower preparation cost and exhibits higher mass specific activity and economy, further proving that the Ru / NC catalyst has the potential to replace the commercial Pt / C catalyst.

[0080] According to the LSV curve ( Figure 7 (b) The Tafel slopes obtained by analysis further reveal the kinetic performance of Ru / NC (50.36 mV / dec), Ru / C (56.64 mV / dec), Ru / N-XC72C (111.47 mV / dec), Pt / C (51.15 mV / dec), and NC (835.5 mV / dec) catalysts. The Ru / NC catalyst exhibits a lower Tafel slope, follows the Volmer-Tafel mechanism, and has excellent kinetic performance.

[0081] Electrochemical impedance spectroscopy (EIS) tests further confirmed the advantages of Ru / NC catalyst in kinetic performance, such as Figure 7 As shown in (c), the charge transfer resistance (Rct) of Ru / NC catalyst is the lowest, which is 39.96Ω. In the comparison of different carbon carriers, the impedance of Ru / N-XC72C is as high as 113.6Ω, which confirms that NC exhibits better conductivity than commercial carbon black (XC72C). Finally, in the comparison between Ru / NC and commercial Pt / C catalyst (Rct = 62.35Q), Ru / NC exhibits better conductivity and HER catalytic performance.

[0082] The chronopotentiometry was performed using a constant current at 10 mA / cm 2 The long-term stability performance of Ru / NC catalyst was evaluated at a current density of . Figure 8 As shown in the figure, the catalyst was in 1M KOH electrolyte, and after continuous electrolysis for 1500 min, the Ru / NC sample showed excellent stability, proving its remarkable stability in the alkaline hydrogen evolution process. This high stability comes from the stable structure and excellent corrosion resistance of the carrier, as well as the confinement effect caused by the appropriate pore structure and pore size, which can effectively curb Ostwald ripening and limit the growth of Ru nanoparticles.

[0083] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.

Claims

1. A method for preparing a self-supporting, tunable pore structure, orderly metal distribution, three-dimensional electrocatalyst, comprising the following steps: 1) Porous organic polymers were prepared by ice template method; 2) dissolving the metal precursor in an ethanol solution at room temperature, and mixing it with the porous organic polymer carrier obtained in step 1), stirring it, and standing it until the ethanol is completely volatilized to obtain a porous organic polymer with orderly metal distribution; 3) Carbonizing the porous organic polymer with orderly metal distribution obtained in step 2) at high temperature to obtain the self-supporting, three-dimensional electrocatalyst with adjustable pore structure and orderly metal distribution.

2. The preparation method according to claim 1, characterized in that: In the step 1), the method for preparing the porous organic polymer specifically comprises the following steps: preparing a polymer precursor emulsion, wherein the emulsion comprises a reactive monomer, a redox initiator, a crosslinking agent, and a reactive emulsifier; subjecting the polymer precursor emulsion to low-temperature freezing and molding; after molding, subjecting the frozen sample to low-temperature polymerization, and after the polymerization is completed, freeze-drying the frozen sample to remove the ice template to obtain a porous organic polymer; Further, the reactive monomer is selected from at least one of the following: methyl methacrylate, acrylonitrile, methacrylamide, and butyl acrylate; Further, the redox initiator includes benzoyl peroxide and N,N-dimethylaniline; Further, the cross-linking agent is selected from ethylene glycol dimethacrylate; Further, the reactive emulsifier is selected from the ADEKAREASOAP series, ER-10; Furthermore, the low-temperature freezing molding uses liquid nitrogen to cool to shape; Furthermore, the reaction conditions of the low-temperature polymerization are: low-temperature polymerization at -15°C to -30°C for at least 12 hours, under the conditions of the low-temperature polymerization, the monomer droplets are completely coalesced and freeze-polymerized.

3. The preparation method according to claim 1 or 2, characterized in that: In the step 2), the metal precursor is selected from at least one of the following: nickel chloride, cobalt chloride, gallium chloride, rubidium chloride, and ruthenium trichloride; And / or, in step 2), the volume fraction of ethanol in the ethanol solution is 90-99.9%; And / or, in step 2), the concentration of the metal precursor in the ethanol solution is 8 mg / L-50 mg / L; And / or, in the step 2), the stirring time is 22 to 26 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step 3), the high temperature carbonization conditions are: heating at a heating rate of 2-5°C / min under a nitrogen atmosphere, heating to 700-800°C and keeping the temperature for 2h.

5. A method for preparing a self-supporting, tunable pore structure, orderly metal distribution, three-dimensional electrocatalyst, comprising the following steps: a) preparing porous organic polymers with orderly metal distribution by ice template method; b) carbonizing the porous organic polymer with orderly metal distribution obtained in step a) at high temperature to obtain the self-supporting, pore structure-adjustable, metal-ordered distributed, three-dimensional electrocatalyst.

6. The preparation method according to claim 5, characterized in that: In the step a), the method for preparing a porous organic polymer with orderly metal distribution specifically comprises the following steps: preparing a polymer precursor emulsion, wherein the emulsion comprises a reactive monomer, a redox initiator, a crosslinking agent, a reactive emulsifier, metal nanoparticles or a metal precursor; subjecting the polymer precursor emulsion to low-temperature freezing and molding; subjecting the frozen sample to low-temperature polymerization after molding, and after the polymerization is completed, freeze-drying the frozen sample to remove the ice template, thereby obtaining a porous organic polymer with orderly metal distribution; Further, the reactive monomer is selected from at least one of the following: methyl methacrylate, acrylonitrile, methacrylamide and butyl acrylate; Further, the redox initiator includes benzoyl peroxide and N,N-dimethylaniline; Further, the cross-linking agent is selected from ethylene glycol dimethacrylate; Further, the reactive emulsifier is selected from the ADEKAREASOAP series, ER-10; Furthermore, the metal nanoparticles or metal precursors are selected from at least one of the following: nickel chloride, cobalt chloride, gallium chloride, rubidium chloride, and ruthenium trichloride; Furthermore, the low-temperature freezing molding uses liquid nitrogen to cool to shape; Furthermore, the reaction conditions of the low-temperature polymerization are: low-temperature polymerization at -15°C to -30°C for at least 12 hours; under the conditions of the low-temperature polymerization, the monomer droplets are completely coalesced and freeze-polymerized.

7. The preparation method according to claim 5 or 6, characterized in that: In the step b), the high temperature carbonization conditions are: heating at a heating rate of 2-5°C / min under a nitrogen atmosphere, heating to 700-800°C and keeping the temperature for 2h.

8. A self-supporting, three-dimensional electrocatalyst with adjustable pore structure and orderly metal distribution prepared by the method of any one of claims 1 to 7.

9. Use of the self-supporting, pore structure-adjustable, metal-ordered distributed, three-dimensional electrocatalyst as described in claim 8 in hydrogen production by water electrolysis.

10. A method for producing hydrogen by electrolyzing water, characterized in that: The method adopts the self-supporting, pore structure-adjustable, metal-ordered distributed, three-dimensional electrocatalyst as described in claim 8 as the electrocatalyst.

Citation Information

Patent Citations

  • Metal nanoparticle-foamy carbon catalyst, and preparation method and application thereof

    CN105013490A

  • Two-dimensional ordered mesoporous carbon sheet and preparation method and application thereof

    CN105523538A

  • Preparation method and application of high-efficiency hydrogen evolution catalyst Ir@NBD-C

    CN111558390A

  • Method of preparing a porous carbon material

    US20170240424A1

Cited By

  • Nylon aerogel for 3D printing and preparation method and application thereof

    CN121159933A